Has piracy in Lithuania really come to an end? Present and future perspectives - Buzaitė, Airida; Dambrauskaitė, Aušrinė (Vilnius University Open Series, 2020)
Piracy is a serious problem that every nation faces. Public authorities deciding to reduce the activity of unlawful content distribution sites encounter a difficult task – balancing copyright protection with the interests of consumers. Decisions made by the Lithuanian radio and television commission to block sites such as filmai.in, torrent.ai and linkomanija.net have prompted public debate on how copyright protection works in practice. This article reviews the concept of blocking and compensation for damage caused, court decisions on the use of these methods and why they do not prevent privacy, also proposing new ways of dealing with piracy that has not been used in Lithuania.